Slope Stability and Land Use in Mountain Valleys - Eisbacher, R. H. (Geoscience Canada, 1982)
Recreational activities and increasing resource development in the highest parts of the Canadian Cordillera will result in permanent high-density settlements along the flanks of hitherto secluded mountain valleys. In this environment the possibility of damage to human works, such as transportation routes and towns, by debris flows or large-scale slope failure has to be appraised, preferably prior to the onset of major construction activity. Two millennia of documented adjustments of settlement pattern to a variety of slope conditions in the densely populated European Alps offer a number of alternatives in approaching this problem by active (technical) or passive (zoning) measures and by the recognition of the residual risk. For areas of proposed permanent housing, mass movements with a projected rate of recurrence of more than one event in 100 to 300 years should be assessed seriously. In precipitous mountain valleys there are very few areas for which risk can be assumed to be nil - particularly if projected time intervals are in excess of 500 years. A certain amount of residual risk thus has to be accepted by those inhabiting or moving through high mountain terrain. Quality of sloping terrain will also figure increasingly in comprehensive resource management (forests, tourism, fishing, and transportation).